Studi Kandungan Protein Susu Jagung Manis pada Lama Perebusan - Ansar, Ansar (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2024)
The types of processed corn in the market still lack diversity so that people in general lack knowledge about the types of processed foods from corn. One of the efforts to provide added value to sweet corn is to process it into corn milk. This study aims to determine the optimum boiling time for the protein content of corn milk. The length of boiling was 10 minutes, 20 minutes, 30 minutes respectively using stove temperature heat which is 35°C, and analyzing the protein content of corn milk using the Kjedahl method. The results showed that the protein content of corn milk was 1.4 grams, 0.9 grams and 0.7 grams per 100 grams’ sample, respectively. The boiling time of Bonanza F1 sweet corn milk affects its protein content, the longer the boiling time the lower the protein content.